Multi-Objective Optimization in Intelligent Decision Support Systems - Sirodgea, I. B.; Kuzomin, А. Ya.; Shtukin, M. V. (Інститут проблем реєстрації інформації НАН України, 2012)
Development of methodology of a complex solution of a problem of decision making in conditions multi-objective optimization and uncertainties of the data fixed classes on the basis of intellectual models and methods of engineering of quantum engineering knowledge has been carried out. Refs: 22 titles.